A computational fluid dynamics analysis of the aerodynamic influence of angles of attack on the Skylon spaceplane - Vivekamanickam Koothan Venkateswaran; Unai Fernandez Gamiz; Ana Boyano; Jesus Maria Blanco (AIP Advances)
This paper explores the aerodynamic behavior of a reusable launch vehicle, the Skylon spaceplane, for different angles of attack at Mach 5. The goal is to determine how aerodynamic effects manifest at various angles of attack and compare it with the theoretical data along with the determination of total time required for such computational fluid dynamics (CFD) simulations. The analysis focuses on the aerodynamics of the Skylon spaceplane and the Synergistic Air-Breathing Rocket Engine to understand their impact on single-stage reusable vehicles in the aerospace sector. This work is also crucial for paving the way for CFD simulations in future research in this sector. The total time consumed by the simulation and the possibility of using its data for other less time-consuming methods, such as convolutional neural networks, are considered. This research establishes a foundation for understanding the aerodynamic effects of specific angles of attack by comparing theoretical and simulation values. Results are produced for angles of attack of −60°, −45°, −30°, −15°, 0°, +15°, +30°, +45°, and +60° at Mach 5. The lift coefficient CL and drag coefficient CD are analyzed using the shear-stress transport k–ω model, and a comparison is made between the theoretical and simulated values. Finally, errors are calculated to understand the variation between the computed and theoretical values, as experimental data comparison is expensive and experimental data are often confidential.